THE EFFECTS OF REGULAR PHYSICAL ACTIVITY ON MOTOR DEVELOPMENT - Kirandi, Özlem; Şahin, Mustafa (Acta Scientiae et Intellectus, 2024)
The aim of this study that lasted for 12 weeks in primary school children aged 7-10 years is to examine the effects of game-based movement education studies on motor development. 128 volunteer children (male n = 72, female n = 56) participated in the study which was conducted in a special etude center in Istanbul after taking written consent from their parents. Preliminary measurement data has been formed by measuring children’s age, height, weight, claw strength, flexibility, balance skills, vertical jump skills, quickness, and speed parameters. The children who brought written consent from their parents to take part in physical activities formed the experimental group (n=67, male 38, female 29); the others who would not take part in the physical activities due to various reasons formed control group (n=61; male 34, female 27). Various activities including game-based movement studies which would develop flexibility, quickness, coordination, speed, aerobic endurance, and strength have been applied to the participants for 12-week with 30-minutes 5 days in a week program in the special etude center’s playground. In the last week of the movement education, last measurement data has been formed by re-measuring the parameters taken in preliminary measurement. The obtained data have been analyzed with descriptive statistics, independent sample t-test and matched sample t-test by using SPSS 20.0 program. As a result of the analyzes done, it was found that the physical activities that were performed during the twelve weeks had more positive effects on many parameters in the experimental group than the children in the control group, between 7 and 10 years, and this situation was determined to express difference in the level of p<,05 and p <,01. As a result, in this direction, it is stated that game-based movement education studies that lasted for 12-weeks have a positive effect on 7-10 years old children. It would be a crucial application for doing studies which would increase physical activity habits in this age group’s alma mater in the name of raising healthy generations. Keywords: Game,